The effect of listening to techno music on reaction times to visual stimuli Účinky poslechu techno hudby na dobu reakce na vizuální podněty - Damir Karpljuk; Maja Meško; Vojko Strojnik; Mateja Videmšek (Palacky University, 2009)
The aim of the research was to establish the influence of techno music on the reaction times of participants in the research. Our hypothesis was that stimulating music, such as techno, would shorten the participants' reaction time to visual stimuli while, without music, the reaction time would be longer. To define the reaction time to expected light stimuli we used a special apparatus for measuring the angle of elbow extension, an electric goniometer and a red colour LED diode attached to it. We also used a computer programme as well. The athletes, 10 students at the Faculty of Sports, aged between 20 and 45, participated in the research, representing the control group as well as the experimental group. In our research we established that listening to techno music does affect the shortening of participants' reaction time. Their reaction time shortens significantly according to a measurement taken after 30 minute of listening to techno music, nevertheless it is not shortened during the listening. The control group established that 35 minutes of waiting between the measurements does not significantly affect the reaction time. Moreover, it was established that 30 minutes of listening to techno music affected the shortening of the reaction time 45 seconds after the music was turned off. For further research, it would be necessary to engage more participants. However, the research results are useful data and may serve as a starting point for further research. Cílem výzkumu bylo stanovit míru vlivu techno hudby na reakční časy účastníků výzkumu. Naše hypotéza byla ta, že stimulující hudba, například techno, zkracuje dobu reakce účastníků na vizuální podněty, zatímco bez hudby je reakční čas delší. K určení doby reakce na očekávané světelné podněty jsme použili speciální zařízení na měření úhlu extenze lokte, elektrický goniometr a k němu připevněnou červenou LED diodu. Také jsme používali počítačový program. Výzkumu se zúčastnili sportovci, 10 studentů Fakulty sportu, ve věku 20 až 45 let, kteří představovali kontrolní i experimentální skupinu. V našem výzkumu jsme zjistili, že poslech techno hudby zkracuje reakční doby účastníků. Dle měření provedených po 30 minutách poslechu techno hudby se jejich doba reakce významně zkracuje, nicméně nezkracuje se během poslechu. Kontrolní skupina stanovila, že 35 minut čekání mezi měřeními reakční dobu významně neovlivňuje. Navíc bylo zjištěno, že 30 minut poslechu techno hudby mělo vliv na zkrácení reakční doby 45 sekund poté, co byla hudba vypnuta. Pro další výzkum by bylo nezbytné zapojit více účastníků. Výsledky výzkumu ovšem poskytují užitečné údaje a mohou sloužit jako východisko pro další výzkum.